Dinamika mikroal'ternacij zubca-T elektrokardiogrammy u vysokokvalificirovannych tjaželoatletov pod vozdejstviem sorevnovatel'noj nagruzki - Belyaev, V. S.; Matveev, Yu. A.; Chernogorov, D. N. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2015)
Possibility of carrying out inspection and screening of the functional condition of cardiovascular system at highly skilled weightlifters is substantiated in the article. Under the influence of high competitive pressures the authors identified deviations of dispersion characteristics, which is regarded as predictors of more severe myocardial morphological violations at skilled weightlifters. Further dynamic supervision of influence of maximal training loads on the state of the T-wave microalternations of ECG can be used by the coaching staff for adequate correction of competition and training loads.